Utilização do gênero Urochloa na produção animal - revisão bibliográfica - Moreira, Bruno Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Brazil has the largest commercial bovine herd in the world and is one of the biggest producers and exporters of bovine meat in the world scenario, and this production is predominantly carried out in grazing systems. Of the total pasture areas cultivated in Brazil, 50% are occupied by the grass Urochloa brizantha cv. Marandu. Pasture areas often present different stages of degradation, characterized by the loss of vigor and decrease in forage availability, infestation of invasive plants, occurrence of pests and diseases and soil degradation, factors that are forced by the decrease in the rate stocking and animal weight gain. Nitrogen fertilization is a strategy used as a way of preventing and recovering degraded pastures and as an alternative to increase the productivity of the pasture rearing system, and the success of this management depends on the source of N use, the amount applied, the timing of application and losses of the soil-plant-environment system, and when these factors are considered, the application of nitrogen fertilizers proves to be economically viable and brings benefits to the production system as a whole, as evidenced by the increase in the production rate, forage accumulation and availability, increasing stocking rate in the area, improving pasture structure, greater forage digestibility and better animal performance.

O Brasil apresenta o maior rebanho comercial bovino do mundo e é um dos maiores produtores e exportadores de carne bovina no cenário mundial, sendo que esta produção é predominantemente realizada em sistemas de criação a pasto. Do total das áreas de pastagens cultivadas no Brasil, 50% são ocupadas pela gramínea Urochloa brizantha cv. Marandu. As áreas de pastagens, muitas vezes, apresentam diferentes estágios de degradação, caracterizados pela perda de vigor e queda na disponibilidade de forragem, infestação de plantas invasoras, ocorrência de pragas e doenças e degradação do solo, fatores estes que são responsáveis pela diminuição na taxa de lotação e do ganho de peso animal. A adubação nitrogenada é uma estratégia utilizada como forma de prevenção e recuperação das pastagens degradadas e como uma alternativa para o aumento da produtividade do sistema de criação a pasto, sendo que o sucesso deste manejo depende da fonte de N utilizada, da quantidade aplicada, da época de aplicação e das perdas do sistema solo-planta-ambiente, sendo que, quando estes fatores são considerados, a aplicação de fertilizantes nitrogenados se mostra viável economicamente e traz benefícios ao sistema de produção como um todo, comprovados pelo aumento da taxa de produção, acúmulo e disponibilidade de forragem, aumento da taxa de lotação da área, melhoria da estrutura do pasto, maior digestibilidade da forragem e maior desempenho animal.
Use of the genus Urochloa in animal production - bibliographical review
Keywords: Bovino de corte; Pastagens Adubos e fertilizantes; Pastagens manejo; Forragem; Gado